2015
DOI: 10.1111/1552-6909.12552
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Use of Social Media Among First‐Time African American Mothers

Abstract: Objective To describe the use of social media during the antepartum and postpartum periods among first-time African American mothers and their support persons. Design A qualitative critical ethnographic research design within the contexts of Family Life Course Development Theory and Black Feminist Theory. Setting Participants were recruited from community-based, public health, and home visiting programs. Participants A purposive sample was recruited, consisting of 14 pregnant African American women and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
0
17

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 25 publications
11
145
0
17
Order By: Relevance
“…Further, findings from this qualitative study elicit the notion that certain pro-breastfeeding social media groups could be considered a pillar of support for breastfeeding mothers, which is consistent with findings that mothers seek support online through social media groups [21]. As there is miniscule information on how social media groups support breastfeeding mothers, these results and findings shed light on topics not previously covered through traditional "mothering" groups and/or bring up novel areas for providing support to breastfeeding mothers.…”
Section: Discussionsupporting
confidence: 82%
“…Further, findings from this qualitative study elicit the notion that certain pro-breastfeeding social media groups could be considered a pillar of support for breastfeeding mothers, which is consistent with findings that mothers seek support online through social media groups [21]. As there is miniscule information on how social media groups support breastfeeding mothers, these results and findings shed light on topics not previously covered through traditional "mothering" groups and/or bring up novel areas for providing support to breastfeeding mothers.…”
Section: Discussionsupporting
confidence: 82%
“…Such reduced use could be the result of women having less time to spend using apps following the birth of their infants, and also their increased use of mother-baby groups and internet sites for information and support 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The researchers suggest that websites and apps may be particularly helpful for women from socioeconomically disadvantaged groups, who may lack access to other sources of information and advice 13 . Other research involving African-American first-time mothers found that they were more engaged with apps on pregnancy and parenting than with the pamphlets they received from their health carers 14 . A large-scale national online survey conducted with American women who had recently given birth found that 56% of first-time mothers rated pregnancy apps as providing very valuable information, as did 47% of experienced mothers.…”
Section: Pregnancy and Parenting Appsmentioning
confidence: 99%
“…Almost all of the study show that mobile health application help mother and father to enhance health status on her pregnancy especially for working mom (Chaves et al, 2017;Premji, 2014;Jennings et al, 2016;Obasola, Mabawonku, & Lagunju, 2015;Felicie et al, 2016;Ledford et al, 2016;Mcnabb et al, 2015, Waring et al, 2014Spiby et al, 2014, Asiodu et al, 2015Rhyne & Borawski, 2014;Guerra-reyes et al, 2017;Smith) . Inline with previous study from Western countries, the 7 studies from non-Western countries including Africa, India, Bangladesh, Australia found that mobile health can give positive impact for pregnant mom Balakrishnan et al, 2016;Forti, Stapleton, & Kildea, 2013;Huq, Azmi, Quaiyum, & Hossain, 2014;Khatun et al, 2015;Lupton & Pedersen, 2016;Khatun et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Based on research conducted by Asiodu et al (2015), mostly postpartum mothers search for information on breastfeeding techniques and infant development through applications in their smartphones. This study shows family support for postpartum mothers by using the application to search for such information.…”
Section: Mobile Health Utilization In Maternity Nursing Care In the Pmentioning
confidence: 99%